IMPACT OF HEPATITIS B GENOTYPES AND TIME OF VACCINE LAST DOSE ON VACCINE BREAKTHROUGH INFECTIONS AMONG VACCINATED SUBJECTS IN BAUCHI STATE, NIGERIA - Mallam Thomas, Kyauta; Bitrus, Joshua B; Titus, Mispha; Anthony, John (FUDMA Journal of Sciences, 2026)
Abstract Hepatitis B Virus (HBV) infection is a major global public health concern. It contributes significantly to liver cirrhosis/hepatocellular carcinoma. The introduction of HBV vaccination into the national immunization program has reduced its incidence. Despite the vaccination, breakthrough infections remain a challenge. A cross-sectional study was carried out on one hundred and ninety-six vaccinated subjects within the ages of 1 year to 50 years, among both sexes who had received at least 2 doses of HB vaccine. The aim was to investigate the pattern of HB vaccine breakthrough infections with a focus on the relationship between immunogenicity and time of last dose of vaccine. The vaccine immunogenicity titre was determined by ELISA. The samples were screened for seromarkers; those positive for HBsAg were tested for HBV DNA and subsequently genotyped by Polymerase chain reaction. The result indicated that vaccinated individuals between the ages of 1-10 years had 61% vaccine optimal vaccine response, while subjects above 10 years had the lowest rate of vaccine response. Additionally, subjects who received the vaccine 1-5 years ago had 64.9% optimal vaccine response, whereas those who received their last dose more than 5 years ago showed a lower rate. Similarly, 3.5% vaccine breakthrough infection was detected, and all had mixed genotypes B and E. This implies that exposure to HBV genotypes B and E may cause breakthrough infection among vaccinated subjects. There is a need for diagnosing hepatitis B infection at the genotype level.